2014
DOI: 10.4314/ahs.v13i4.8
|View full text |Cite
|
Sign up to set email alerts
|

Counselling at primary health facilities and level of knowledge of antenatal attendees and their attitude on prevention of Mother to Child Transmission of HIV in Dar-es salaam, Tanzania

Abstract: Background: Children living with HIV worldwide majority are infected through mother to child transmission of HIV (MTCT) acquired during pregnancy. Knowledge, attitude and behavioral changes are pivot tools towards success of any interventions. Objectives: To determine the effectiveness of counseling on HIV done in primary health facilities (PHF), level of knowledge gained and attitude changes towards PMTCT. Methods: A cross sectional study assessing pregnant women's knowledge and their attitude towards PMTCT w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
3
7
2
Order By: Relevance
“…In this study education level of secondary and above were 5.4 times (AOR = 5.4, 95% CI 2.69-10.98) more likely to be knowledgeable on PMTCT of HIV than those with no formal education. This explanation is in line with the study done in, Addis Ababa, Hawassa and Tanzania [8,11,12]. This could be because when the women become educated their health seeking behavior and access to information might be increased.…”
Section: Discussionsupporting
confidence: 83%
“…In this study education level of secondary and above were 5.4 times (AOR = 5.4, 95% CI 2.69-10.98) more likely to be knowledgeable on PMTCT of HIV than those with no formal education. This explanation is in line with the study done in, Addis Ababa, Hawassa and Tanzania [8,11,12]. This could be because when the women become educated their health seeking behavior and access to information might be increased.…”
Section: Discussionsupporting
confidence: 83%
“…The frequently mentioned reason for not up taking VHCT service in this study was fear of stigma and discrimination both in qualitative and quantitative (40.9%) results. This finding was supported by studies in Northwest Ethiopia [9,11] and other studies [9,12,22,16,17,[25][26][27][28]. The reason of no tested for HIV in about 63.5% pregnant mothers in North-West Ethiopia was fear of rejection by the community if result become positive [9].…”
Section: Discussionsupporting
confidence: 55%
“…This study found 70.5% of women in Zimbabwe had correct comprehensive knowledge of MTCT and PMTCT. This finding was higher than 34.9% reported in Ethiopia [8], 60% in Tanzania [18], 50% in Uganda [19], and 58.6% in the United States of America [20]. On the other hand, it was lower than 78% in Nigeria [21].…”
Section: Discussionmentioning
confidence: 64%